PENGARUH PEMBERIAN EKSTRAK ETANOL BUAH AREN (Arenga pinnata Merr.) TERHADAP PROFIL DARAH TIKUS PUTIH (Rattus norvegicus L.) YANG DIINDUKSI KARBON TETRAKLORIDA (CCl4) - Triyudha, Garibaldi; Febriani, Husnarika; Aisyah Hutasuhut, Melfa (Universitas Cokroaminoto Palopo, 2025)
Carbon tetrachloride (CCl4) is a common sanitizer and decomposer that can be harmful if eaten, inhaled, or absorbed through the skin. Herbal plants can be used as therapeutic treatment to counteract the effects of these dangerous drugs. Palm fruit (Arenga pinata Merr) is one of them. The aim of this research was to determine the effect of administering palm fruit extract on the number of erythrocytes, leukocytes, hemoglobin and platelets in white rats induced by carbon tetrachloride.This study used a completely randomized design with 20 mice divided into 5 treatment groups. Negative controls were given food, drink and 1 ml/kg BW olive oil, positive controls were given 1 ml/kg BW carbon tetrachloride and olive oil with a ratio of 1:3. Treatments 1, 2 and 3 were given carbon tetrachloride 1ml/kg BW and olive oil with a ratio of 1:3 and given ethanol extract of palm fruit at different doses (P1= 90 mg/kg BB, P2= 180 mg/kg BB, P3= 360 mg/kg BB) for 15 days. The results obtained include that the ethanol extract of palm fruit has a very significant effect on erythrocytes, hemoglobin, leukocytes and platelets with a P value = 0.000 and the average value of erythrocytes (7.66 µl), hemoglobin (13.45 g/dl), leukocytes (15 .34 µl), platelets (895.25 mm²). The optimal dose of palm fruit extract to counteract and improve the number of erythrocytes, hemoglobin, leukocytes and platelets is a dose of 360 mg/kg BB.